Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2021)
A dataset containing 277246 species occurrences available in GBIF matching the query: { "and" : [ "BasisOfRecord is Specimen", "Country is Japan", "HasCoordinate is true", "HasGeospatialIssue is false", "OccurrenceStatus is Present", { "or" : [ "Year is 1955", "Year is 1960", "Year is 1965", "Year is 1970", "Year is 1975", "Year is 1980", "Year is 1985" ] } ] } The dataset includes 277246 records from 334 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0068046-210914110416597/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences